Influence of Leadership Style and Compensation Against Employee Performance Through Motivation (Case Study On Employee of Production Department of PT. Dwimatama Multikarsa, fertilizer packing unit, Tanjung Emas Semarang) - Dias Dias (Jurnal Ilmu Administrasi Bisnis, 2012)
can affect the performance of the employees. Among them is the style of leadership, compensation and motivation. The purpose of this study was to determine how far the influence of the leadership style t and compensation hrough motivationon employee performance. The problem in this research is the company has already provided adequate compensation and leadership style that is able to communicate well and motivated employees to be more passion in work , but performance of employees assigned has never been achieved. This study uses the type of explanatory research studies on PT. Dwimatama Multikarsa, sampling technique used is Simple random sampling. The technique of collecting data was made through questionnaires. Data were statistically analyzed with simple linear regression, regression, t test, F test, and path analysis.The results of the calculation is Y2 = 11.316 + 0.267 + 0.597 X1 + 0.915 X2 Y1, indicating that the leadership style (X1), compensation (X2) and motivation (Y1)  positively influence  employee performance (Y2), which means that the better assessment of respondents' leadership style, compensation and motivation lead to higher performance for PT. Dwimatama Multikarsa, fertilizer packing unit, Tanjung Emas Semarang. It can be proved that the style of leadership and compensation through  motivation affect  employee performance. The conclusion of this study is that there is influence of leadership style, compensation and motivation on employee performance of PT.Dwimatama Multikarsa. Advice: Compensation generally has been good and in accordance with the minimum wage prevailing in the area, but the need for and type of work and duration of work , must be  kept in mind.